GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 2338 species occurrences available in GBIF matching the query: TaxonKey: Lampetra fluviatilis (Linnaeus, 1758) HasCoordinate: true HasGeospatialIssue: false. The dataset includes 2338 records from 61 constituent datasets: 5 records from National System of Protected Areas in Poland - Animals. 583 records from Biological Records Centre - Database for the Atlas of Freshwater Fishes. 131 records from NRM-Fishes. 406 records from Artdata. 1 records from Biodiversity records from Ireland - general. 1 records from Estonian Nature Observations Database. 9 records from Limnodata. 75 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 116 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 19 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Vertebrate Observation Records, other than Birds. Pre-2010 for Cumbria. 6 records from Geographically tagged INSDC sequences. 1 records from Scottish Environment Protection Agency - Selected Scottish freshwater fish records from 2008-2011 (collected by SEPA). 86 records from Inventaire National du Patrimoine Naturel : Atlas des poissons d'eau douce de France métropolitaine (2011). 127 records from SLU Aqua Institute of Freshwater Research Swedish Electrofishing Registry - SERS. 9 records from naturgucker. 2 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 9 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 6 records from RAVON (NL) - Fish observations extracted from Hoek (1890) and Redeke (1921). 5 records from Freshwater fishes of Italy. 1 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 4 records from Ichthyology. 1 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 3 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD unverified freshwater fish data up to current day. 9 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 1 records from Monitoring data from the federal state Saxony (Germany). 4 records from Fish collection, Natural History Museum, University of Oslo. 2 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 2 records from Merseyside BioBank - North Merseyside Fish (unverified). 10 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 154 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 2 records from EPA'S EMAP Database. 7 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 12 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 10 records from Fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 81 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 2 records from Australian Museum provider for OZCAM. 1 records from Natural History Museum Rotterdam (NL) - Chordata collection. 1 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 2 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 27 records from Countryside Council for Wales - Lamprey Survey Data. 2 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 2 records from Biological and palaeontological collection and observation data MNHNL. 4 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 168 records from Atlas of Danish Fishes. 30 records from Royal Dutch Angling Association (SVN) - Piscaria. 1 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 1 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 120 records from Trekvis - Migratory fishes in the river Scheldt. 1 records from SLU Aqua Institute of Coastal Research Database for Coastal Fish - KUL. 1 records from Collection Pisces SMF. 5 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 38 records from NINA Vanndata fisk. 5 records from Royal Netherlands Institute for Sea Research (NIOZ) - Kom Fyke Mokbaai. 4 records from Historical hyperbenthos data (1987-2001) from the North Sea and some adjacent areas (EurOBIS). 7 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 1 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 3 records from CAS Ichthyology (ICH). 2 records from Ichthyology Collection - Royal Ontario Museum. 8 records from Museum of Comparative Zoology, Harvard University. 1 records from Fishbase. 1 records from Priest Pot species list, Cumbria, Britain.
Keywords: GBIF; biodiversity; species occurrences